ADEQUACY OF COMMUNICATION CHANNELS FOR MATERNAL HEALTHCARE IN DELTA STATE - OZIWELE, Eloho Patience (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
This study examined the adequacy of communication channels available for maternal healthcare in Delta State. Rationalized by the agenda setting theory, the quantitative and qualitative research designs, the questionnaire was used to extract relevant information from a sample size of 399 respondents. The study found that the level of awareness of the programmes was encouraging for FMHCP and HeFAD. The majority of respondents acknowledged that the communication channels were adequate, and more than half thought they were effective in influencing participation in the maternal healthcare programmes. The stakeholders acknowledged the use of multiple communication channels in spreading awareness of the maternal healthcare programmes. Therefore, the study recommends the continuous usage of communication channels to spread awareness of maternal healthcare programmes.